2007
DOI: 10.1080/15572536.2007.11832601
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships among Ascochyta species infecting wild and cultivated hosts in the legume tribes Cicereae and Vicieae

Abstract: Evolutionary relationships were inferred among a worldwide sample of Ascochyta fungi from wild and cultivated legume hosts based on phylogenetic analyses of DNA sequences from the ribosomal internal transcribed spacer regions (ITS), as well as portions of three protein-coding genes: glyceraldehyde-3-phosphate-dehydrogenase (G3PD), translation elongation factor 1-alpha (EF) and chitin synthase 1 (CHS). All legume-associated Ascochyta species had nearly identical ITS sequences and clustered with other Ascochyta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 45 publications
5
64
0
Order By: Relevance
“…However, the pathogen was able to infect other leguminous and non-leguminous hosts, which may increase its potential for survival and spread. Hernandez-Bello et al (2006) and Peever et al (2007) also demonstrated that interspecific crosses between closely related, but host-specific Ascochyta spp. such as A. fabae and A. pisi, were fertile but most a Dried and sterilised stem and leaf pieces were inoculated with two sexually compatible isolates of Didymella rabiei and incubated in the dark at 8°C and alternating relative humidity for 8 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…However, the pathogen was able to infect other leguminous and non-leguminous hosts, which may increase its potential for survival and spread. Hernandez-Bello et al (2006) and Peever et al (2007) also demonstrated that interspecific crosses between closely related, but host-specific Ascochyta spp. such as A. fabae and A. pisi, were fertile but most a Dried and sterilised stem and leaf pieces were inoculated with two sexually compatible isolates of Didymella rabiei and incubated in the dark at 8°C and alternating relative humidity for 8 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…Steele and Wojciechowski (2003) identified two subclades within the Vicieae including Clade 1 which contained P. sativum and Clade 2 which contained L. culinaris and V. grandiflora. Although there was not complete overlap in the hosts sampled for the Steele and Wojciechowski (2003) study and our study (Peever et al 2007), there appears to be broad congruence between pathogen and host phylogenies with the Steele and Wojciechowski (2003) Clade 1 corresponding to the A. pisi/A. fabae clade in the combined analysis reported here and the Steele and Wojciechowski (2003) Clade 2 corresponding to the A. lentis clade reported here (Fig.…”
Section: Species Of Ascochytamentioning
confidence: 50%
“…Phylogenetic analyses of the combined G3PD, CHS and EF datasets using maximum likelihood methods revealed that A. rabiei, the pathogen of chickpea (C. arietinum), was distinct from the Ascochyta pathogens of pea, faba bean, wild vetches and lentil which were found in two differentiable but closely related clades ( Fig. 1, Peever et al 2007). The differentiation observed between A. rabiei and A. lentis/A.…”
Section: Species Of Ascochytamentioning
confidence: 98%
See 1 more Smart Citation
“…Molecular study of Ascochyta pathogens isolated from a number of legume species (wild and domesticated) enabled the assessment of the phylogenetic relationships among the sampled group (Barve et al 2003;Peever et al 2006). Like the host plants that undergo speciation processes on an evolutionary time scale, the pathogens are adjusting themselves to the evolutionary trends of their hosts as expected from the intimate interactions that occur through most of the life cycle of the pathogen.…”
Section: Host-pathogen Coevolutionmentioning
confidence: 99%